SCIENTIFIC INNOVATIVE DEVELOPMENT OF COTTON GINING - Abdullayev, Ravshan (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Today, it is becoming very important to conduct a thorough and serious study of the question of whether roller and saw gins used in the world cotton ginning industry for ginning fine and medium staple cotton cause mechanical damage to the fibers. The results of the conducted scientific and practical studies show that the working element of the saw gins is a cylinder made of saw blades, which, as has been established, negatively affects the quality of the fiber and seeds in the process of joint operation of the grate with saw blades to separate the fiber from the seeds.